Penerapan Metode Terjemah Bahasa Jawa pada Al Qur’an dan Hadits - Erwin Maulana Pramudita; Anita Puji Astutik (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This study aims to explore the application of Javanese translation methods in Al Fattah Islamic Boarding School in Sidoarjo. The translation method in this pesantren uses two main approaches: Tarjamah ḥarfiyyah (literal) and tarjamah tafsiriyyah (interpretive), which ensures a deep understanding for the students. The results show that this translation method not only enhances religious understanding but also plays a role in preserving local culture. Santri feel closer to the teachings of Islam because they can understand them in their mother tongue, Javanese. In addition, the translation enriches the Javanese vocabulary and strengthens its position in the religious context. The integration of Islamic teachings with Javanese culture through translation also increases appreciation and understanding of the teachings, and supports the preservation and development of local culture. Another positive impact is the improvement of the quality of da'wah in local communities, as Islamic teachings are delivered in a more relevant and acceptable way. The research method uses a qualitative method with a phenomenological approach. The phenomenological approach is a qualitative data analysis technique to reveal the common meaning that is the essence of a concept.